Areca nut exposure increases secretion of tumor‐promoting cytokines in gingival fibroblasts that trigger DNA damage in oral keratinocytes. Issue 11 (24th June 2015) - Illeperuma, Rasika P.; Kim, Do Kyeong; Park, Young Jin; Son, Hwa Kyung; Kim, Jue Young; Kim, Jinmi; Lee, Doo Young; Kim, Ki‐Yeol; Jung, Da‐Woon; Tilakaratne, Wanninayake M.; Kim, Jin
Abstract : Molecular crosstalk between cancer cells and fibroblasts has been an emerging hot issue in understanding carcinogenesis. As oral submucous fibrosis (OSF) is an inflammatory fibrotic disease that can potentially transform into squamous cell carcinoma, OSF has been considered to be an appropriate model for studying the role of fibroblasts during early stage carcinogenesis. In this sense, this study aims at investigating whether areca nut (AN)‐exposed fibroblasts cause DNA damage of epithelial cells. For this study, immortalized hNOF (hTERT‐hNOF) was used. We found that the levels of GRO‐α, IL‐6 and IL‐8 increased in AN‐exposed fibroblasts. Cytokine secretion was reduced by antioxidants in AN‐exposed fibroblasts. Increase in DNA double strand breaks (DSB) and 8‐oxoG FITC‐conjugate was observed in immortalized human oral keratinocytes (IHOK) after the treatment of cytokines or a conditioned medium derived from AN‐exposed fibroblasts. Cytokine expression and DNA damage were also detected in OSF tissues. The DNA damage was reduced by neutralizing cytokines or antioxidant treatment. Generation of reactive oxygen species (ROS) and DNA damage response, triggered by cytokines, were abolished when NADPH oxidase (NOX) 1 and 4 were silenced in IHOK, indicating that cytokine‐triggered DNA damage was caused by ROS generation through NOX1 and NOX4. Taken together, this study provided strong evidence that blocking ROS generation might be a rewarding approach for cancer prevention and intervention in OSF. Abstract : What's new? Fibroblasts in the tumor microenvironment influence tumor initiation and growth and are of particular interest in oral submucous fibrosis (OSF), a progressive fibrotic disease of malignant potential. This study shows that the release of tumor‐promoting cytokines by fibroblasts exposed to areca nut, the primary cause of OSF, induce DNA damage in oral keratinocytes. The findings suggest that fibroblasts indirectly promote epithelial transformation in OSF by secreting cytokines, whereby DNA damage of epithelial cells is inflicted by reactive oxygen species generated via NADPH oxidases. These insights could inform the development of new therapeutic approaches for OSF.